(untitled) (Mugda Medical College Journal, 2024)
Background: Chronic otitis media (COM) is a disease of multiple etiology caused by bacteria and its importance lies in its chronicity and awful complications. The microbiological study shows the growth of a lot of organisms, frequently multiple and those differ based on geographical variation, patient population, climate, and many other factors. Objective: To evaluate current bacteriological trends of ear infections in patients with chronic otitis media which will be beneficial for appropriate treatment as well as for reducing complications. The study also focuses on rapid diagnosis by exploring other factors like age and sex-wise distribution, socioeconomic status, distribution of patients according to the type of dwelling, and bathing habits of patients. Methods: This cross-sectional, observational study was conducted in the Department of ENT and Head-Neck Surgery, Rangpur Medical College Hospital in Rangpur, a northern district of Bangladesh, over 6 months on a total of 80 patients who had attended outpatient and inpatient departments. Aural swab was taken from the discharging ears which were inoculated on blood agar and MacConkey’s agar media. The organism pattern was then tabled based on the culture reports. Results: The most common bacteria causing COM was Pseudomonas aeruginosa in (45.0%) followed by Staph. aureus (27.5%), mixed isolates in 8.75%, E. coli in 5%, Proteus in 3.75%, S. pneumoniae in 2.5%, and Klebsiella in 1.25%. Conclusion: The study proved to be useful for clinicians in management of COM and its complications. Early and effective microbiological diagnosis and intervention is the best solution. From this study, it is observed that Pseudomonas aeruginosa is the commonest pathogen for bacterial ear disease followed by S. Aureus. Mugda Med Coll J. 2023; 6(2): 83-87